2020
DOI: 10.1002/jhet.3906
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some 5‐arylidene‐2‐(4‐acetamidophenylimino)‐thiazolidin‐4‐one derivatives and exploring their breast anticancer activity

Abstract: Ten 2‐(4‐acetamidophenylimino)‐5‐arylidenethiazolidin‐4‐one derivatives 6a‐k were synthesized and evaluated for their anticancer activity against MCF‐7 cell line (breast adenocarcinoma). The synthetic approach involves cyclocondensation of N,N′‐bis(4‐acetamidophenyl)‐thiourea (3) with ethyl bromoacetate in ethanol and sodium acetate to furnish the 2‐(4‐acetamidophenylimino)‐4‐thiazolidinone derivative 4, which underwent Knoevenagel condensation reaction with some substituted aldehydes to afford the targeted 2‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…We completed the reaction mix by adding 19 μl of nuclease‐free water. All reactions were performed for 35 cycles using the following temperature profiles: “95°C for 5 min (initial denaturation); 95°C for 15 min (Denaturation), 55°C for 30 min (Annealing), and 72°C for 30 min (Extension)” (Abumelha & Saeed, 2020; Nirwan et al, 2019). Then, the C t values were collected to calculate the relative genes’ expression in all samples by normalization to the β‐actin housekeeping gene (Nafie, Arafa, et al, 2020; Nafie et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We completed the reaction mix by adding 19 μl of nuclease‐free water. All reactions were performed for 35 cycles using the following temperature profiles: “95°C for 5 min (initial denaturation); 95°C for 15 min (Denaturation), 55°C for 30 min (Annealing), and 72°C for 30 min (Extension)” (Abumelha & Saeed, 2020; Nirwan et al, 2019). Then, the C t values were collected to calculate the relative genes’ expression in all samples by normalization to the β‐actin housekeeping gene (Nafie, Arafa, et al, 2020; Nafie et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The thioureas so obtained were cyclized by refluxing with ethyl bromoacetate in the presence of sodium acetate to give the title compounds 160 in good yields. Compound 160a revealed good anticancer activity as determined by the MTT assay with 35.82% inhibition in HeLa cells at a dose of 10 μM while no toxicity was shown against NIH3T3 mouse fibroblast cells at the same dose with a 98.19% survival rate [39] thiazolidinone scaffold by a substituted-benzylidene moiety enhanced the anticancer potential of the 4-thiazolidin one analogues [41].…”
Section: Anticancer Derivativesmentioning
confidence: 99%
“…The in vitro activity as assessed by the MTT assay displayed the remarkable anticancer potential of compound 167a with an IC 50 value of 58.33 μM. The SAR study revealed that the substitution at position 5 of the thiazolidinone scaffold by a substituted‐benzylidene moiety enhanced the anticancer potential of the 4‐thiazolidinone analogues [41].…”
Section: Synthetic Strategies and Biological Activity Profile Of 4‐th...mentioning
confidence: 99%
“…Overexpression of VEGFR1 has been associated with a poor prognosis, as it is thought to contribute to tumor growth and metastasis. [11] Thiazolidin-4-one and its derivatives have a wide range of pharmacological activities such as anticancer [12][13][14][15][16][17] anti-inflammatory, analgesic, anticonvulsant, antimicrobial, local and spinal anesthetics, central nervous system stimulants, hypnotics, anti-HIV, antidiabetic, follicle-stimulating hormone receptor antagonist. [18][19][20][21][22] The aim of this study is to develop new and effective anticancer agents through the synthesis of thiazolidin-4-one derivatives of 4-furfuryloxy-benzohydrazide.…”
Section: Introductionmentioning
confidence: 99%